2002
DOI: 10.1046/j.1365-2133.2002.05012.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of lichen sclerosus

Abstract: These guidelines for the management of lichen sclerosus have been prepared for dermatologists on behalf of the British Association of Dermatologists. They present evidence-based guidance for treatment, with identification of the strength of evidence available at the time of preparation of the guidelines, and a brief overview of epidemiological aspects, diagnosis and investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
2
16

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 80 publications
(117 reference statements)
1
167
2
16
Order By: Relevance
“…Pimecrolimus has a similar mode of action to that of tacrolimus but is more selective and may be better tolerated than topical tacrolimus due to less local irritation. In contrast to topical steroid, there is no potential for pimecrolimus to induce skin atrophy and telangiectasia 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pimecrolimus has a similar mode of action to that of tacrolimus but is more selective and may be better tolerated than topical tacrolimus due to less local irritation. In contrast to topical steroid, there is no potential for pimecrolimus to induce skin atrophy and telangiectasia 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrapotent topical corticosteroids have been the first-line treatment for LSA at any site, the outcomes are variable 3,7,8 . Moreover, there has been no randomized controlled trial comparing therapeutic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although not proven, it has been suggested that the risk of malignancy in uncomplicated genital LS that has been diagnosed and treated appropriately is less. 21 Whilst the relative risk of vulval malignancy in patients with LS of pre-pubertal onset is unknown, SCC of the vulva has been reported prior to the age of 40 years in patients with childhood-onset LS. 3 Genital SCC is known to be associated with the presence of oncogenic HPV genotypes.…”
Section: Associated Malignancymentioning
confidence: 99%
“…The epidermis is atrophic with hydropic degeneration of basal cells and a homogenous pale zone in the upper dermis. 21 There is a lichenoid infiltrate of mainly mononuclear cells in the dermis.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation